Pemberdayaan Perempuan Pegunungan Kota Ambon Melalui Pelatihan Diversifikasi Produk Olahan Perikanan - Hahury, Hendri D.; Siaila, Steven; umerung, Dientje R; Oppier, Hermi; Matitaputty, Izaac T.; Ferdinandus, Sherly; Pattimahu, Terezia V. (Journal Of Human And Education (JAHE), 2024)
Women are always identified with only domestic work. In fact, women are a potential source of income for the sustainability of household livelihoods. Moreover, when compared to men, women have a greater level of tenacity, innovation and creativity than men. This condition is illustrated through the diversification activities of fish products which until now have only been consumed as is. The Community Service Team, Department of Development Economics, FEB, Pattimura University provides training and science and technology diffusion. The training was carried out by means of counseling regarding various diversification of products made from fish, while the science and technology diffusion was in the form of fish sauce products. The results of service activities show that fish products that are easily damaged and rotten can be given added economic value through diversification as well as being an alternative source of income for households in the form of fish sauce. Then, women in Mahia Hamlet have the desire to help their husbands earn additional income, but this desire is often hampered by various obstacles such as knowledge of product diversification and marketing.